Multiplier Effects of Striped Catfish Cultivation Business on the Community's Economy in Kuok Village, Kampar District, Riau Province - Fahrian, Feldi; Warningsih, Trisla; Kusai, Kusai (Faculty of Fisheries and Marine, Universitas Riau, 2024)
This research was conducted in June 2022 in Kuok Village, Kuok District, Kampar Regency, Riau Province. The purpose of the study was to describe the businesses that emerged as having an impact on the existence of the striped catfish farming business and analyze the multiplier effect of the existence of the striped catfish farming business in Kuok Village, Kampar Regency, Riau Province. The survey method was used, and the respondents were determined by purposive sampling. The results showed that economic activities impacting striped catfish farming consisted of fish farming activities, hatchery business units, feed sales business units, and some as workers at CV. Patin Prima can be called labor. The Income Multiplier Ratio, type II, produces a value of 1.01, meaning it economically impacts the community in Kuok Village.